PENGARUH KEMISKINAN TERHADAP PEKERJA ANAK INDONESIA: ANALISIS DATA MIKRO - Arif Maulana; Nugrahayu Suryaningrum (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
Child labor is a form of violence and exploitation of children with economic motives. During the COVID-19 pandemic, there was an increasing percentage of child labor from 2.35 percent in 2019 to 3.25 percent in 2020. This is a consequence of the supply side of child labor, the economic factor behind the availability of child labor. This study aims to analyze the effect of poverty on child labor in Indonesia using data from the March 2020 National Socio-Economic Survey (Susenas) and binary logistic regression analysis. The results showed that the highest percentage of child labor was found in poor households, the lowest 25 percent of per capita expenditure. By conducting a robustness check, the resulting poverty status has a positive and significant impact on the opportunities for child labor in Indonesia. The influence of poverty on child labor opportunities is largely due to household economic factors.